Saints and lovers: myths of the avant-garde in Michel Georges-Michel's Les Montparnos - Shingler, Katherine (Sage, 2012)
This article examines Michel Georges-Michel’s 1924 novel Les Montparnos as a study of the myths circulating around the Montparnasse avant-garde of the 1920s, and their function in relation to art. Key amongst these myths is the idea of art as a religion, according to which avant-garde artists are conceived as secular saints and martyrs. While this notion of artist as saint is strongly present in early-twentieth-century biographies of Van Gogh, Georges-Michel explicitly relates his fictionalized version of Modigliani’s life not to such recent models but rather to the Renaissance masters, and especially to Raphael, a link which is explained in terms of the post-war ‘retour à l’ordre’ in French artistic culture. The novel’s references to Raphael as archetypal painter-lover are also related to its construction of a myth of the artist as virile and sexually prolific, and to its identification of creative and sexual impulses.